Scarlet and black. - Boyd, Kendra; Fuentes, Marisa J.; White, Deborah G. (Deborah Gray), 1949- (Rutgers University Press, 2020)
Scarlet and Black documents the history of Rutgers's connection to slavery, which was neither casual nor accidental--nor unusual. Like most early American colleges, Rutgers depended on slaves to build its campuses and serve its students and faculty. The contributors offer this history as a usable one--to strengthen Rutgers and help direct its course for the future.